ESMO–ESGO consensus conference recommendations on ovarian cancer: pathology and molecular biology, early and advanced stages, borderline tumours and recurrent disease. Issue 4 (2nd May 2019) - Colombo, N; Sessa, C; Bois, A du; Ledermann, J; McCluggage, WG; McNeish, I; Morice, P; Pignata, S; Ray-Coquard, I; Vergote, I; Baert, T; Belaroussi, I; et al.
Abstract : The development of guidelines is one of the core activities of the European Society for Medical Oncology (ESMO) and European Society of Gynaecologial Oncology (ESGO), as part of the mission of both societies to improve the quality of care for patients with cancer across Europe. ESMO and ESGO jointly developed clinically relevant and evidence-based recommendations in several selected areas in order to improve the quality of care for women with ovarian cancer. The ESMO–ESGO consensus conference on ovarian cancer was held on April 12–14, 2018 in Milan, Italy, and comprised a multidisciplinary panel of 40 leading experts in the management of ovarian cancer. Before the conference, the expert panel worked on five clinically relevant questions regarding ovarian cancer relating to each of the following four areas: pathology and molecular biology, early-stage and borderline tumours, advanced stage disease and recurrent disease. Relevant scientific literature, as identified using a systematic search, was reviewed in advance. During the consensus conference, the panel developed recommendations for each specific question and a consensus was reached. The recommendations presented here are thus based on the best available evidence and expert agreement. This article presents the recommendations of this ESMO–ESGO consensus conference, together with a summary of evidence supporting each recommendation.